Prime, shock and kill: BCL-2 inhibition for HIV cure - Chandrasekar, Aswath P.; Badley, Andrew D. (Frontiers in Immunology, 2022)
While modern HIV therapy can effectively suppress viral replication, the persistence of the latent reservoir posits the greatest hurdle to complete cure. The “shock and kill” strategy is under investigation for HIV therapy, aiming to reactivate latent HIV, and subsequently eliminate it through anti-retroviral therapy and host immune function. However, thus far, studies have yielded suboptimal results, stemming from a combination of ineffective latency reversal and poor immune clearance. Concomitantly, studies have now revealed the importance of the BCL-2 anti-apoptotic protein as a critical mediator of infected cell survival, reservoir maintenance and immune evasion in HIV. Furthermore, BCL-2 inhibitors are now recognized for their anti-HIV effects in pre-clinical studies. This minireview aims to examine the intersection of BCL-2 inhibition and current shock and kill efforts, hoping to inform future studies which may ultimately yield a cure for HIV.